An Overview of the Past of Animal Domestication - Adhikari, Ram Chandra (Medha: A Multidisciplinary Journal, 2023)
The study aimed to explore the domestication of animals concerning their advantages, disadvantages and history. The article is based on literature survey. Going through the websites of different academic search engines and agencies literatures were deeply analyzed. There are many breeds of few species of domesticated animals. Pople have been using domesticated animals for many purposes like guard, porter, labor, friends, food, fertilizer, as ornament of houses, as income source, for study and research, experimental purposes, biotechnology, improving the variety and beautify the nature. The study also found that most of the domestic animals of today were domesticated from 11,000 years ago. Dogs were domesticated 35,000 years ago, goat, pig, cow, sheep and other cattle were domesticated in 9500 Before Common Era (BCE) and cats in 7500 BCE. Horse was domesticated 5500 years ago, chicken 4000 years ago and insects were domesticated 5000 years ago. Domestication of animal is essential for the conservation of genetic resource too.